Improving clinical trial enrollment in minority racial and ethnic patients with gynecologic malignancy - Olivia D. Lara; Kathryn Allen; Amin Yakubov; Bhavana Pothuri (Elsevier, 2024)
Purpose: Racial and ethnic minorities remain underrepresented in clinical trials . Underrepresentation of racial groups leads to the selection of therapeutic interventions that may not be representative of the population expected to use the medicine. This study evaluates the effectiveness of a set of implementation strategies to increase underrepresented patients in gynecologic cancer clinical trials. Methods: An interrupted time series analysis evaluating implementation strategies (pre-screening and fast-track referral) was conducted from January 2021 to May 2022. Descriptive analysis of gynecologic oncology patient screening and accrual was compared before and after intervention implementation. Results: During the study period (pre- and post-intervention), 26 patients were screened, and 9 patients enrolled in therapeutic gynecologic cancer clinical trials. Prior to the intervention, 7 patients were screened and 2 patients enrolled onto a clinical trial. Following the intervention, 19 patients were screened and 7 patients enrolled in a cancer clinical trial. Black patients comprised 13 of 19 (68.4%) of patients post-intervention compared to 1 of 7 (14.3 %) of patients screened pre-intervention (p < 0.05). All 7 patients enrolled post intervention were racial and ethnic minorities (non-Hispanic Black [4 of 7] and Hispanic White [3 of 7]) compared to no minority patients enrolled pre-intervention (p < 0.05). Screening increased 2.5-fold for all patients, and 5- fold for minority patients. Clinical trial enrollment increased 3.5-fold following intervention. Conclusions: A combination of pre-screening and fast-track referral intervention in a racial and ethnically diverse urban academic hospital was associated with a significant increase in minority screening and enrollment. Structured strategies to overcome barriers to underrepresented racial and ethnic patient accrual in academic hospitals are urgently warranted.